ممارسات قتل وإعدام الجزائريين خلال حكم السيف 1830-1870 - زقب, عثمان (جامعة الوادي - University of Eloued, 2022)
يشكل القتل والإعدام العشوائي؛ مظهرا معتادا لدى إدارة الاحتلال الفرنسي في الجزائر؛ خاصة خلال فترة الحكم العسكري، وحملات جيش إفريقيا. لقد كانت الحالة الاستثنائية في التعامل مع شؤون الجزائر والمسلمين بالخصوص ذريعة لدى قادة وضباط الجيش الفرنسي لاختراق أبسط قواعد القانون الدولي الإنساني، والاتفاقيات الدولية المنظمة للصراع في حالة الحروب. ولم تكن حالات الإعدام العشوائي التي يخضع لها الجزائريون تستند إلى محاكمات ولو كانت شكلية ماعدا في فترات متقدمة من الحكم العسكري في الجزائر. إن هذه الإعدامات أخذت شكل الحالات الفردية المعزولة؛ غير أنها أيضا اعتمدت أسلوب التصفية الجماعية للسكان المسلمين، ضمن إستراتيجية حرب إبادة مفضوح . constitutes indiscriminate killing and execution; A familiar aspect of the French occupation administration in Algeria; Especially during the period of military rule, and the campaigns of the Army of Africa. The exceptional situation in dealing with the affairs of Algeria and Muslims in particular was a pretext for the leaders and officers of the French army to breach the most basic rules of international humanitarian law, and international conventions regulating conflict in case of war. The random executions that Algerians were subjected to were not based on trials, even if they were formal, except in the advanced periods of the military rule in Algeria. These executions took the form of isolated individual cases; However, it also adopted the method of mass liquidation of the Muslim population, as part of a blatant extermination war strategy.
مقال
Keywords: الإعدام ; العدالة ; الاحتلال ; القمع ; الجزائريين; execution; Justice; Occupation; repression; Algerians